Preparation and Characterization of Polyaniline Film on Conductive Glass for Dye-Sensitized Solar Cell Counter Electrodes by Chemical Deposition - Keothongkham, Khamsone; Pimanpang, Samuk; Maiaugree, Wassan (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objective of this research is to fabricate dye-sensitized solar cells (DSSCs) by chemical deposition method. Polyaniline films were coated on conductive glass for four different deposition times (30, 60, 120 and 180 min). They were then used as the dye-sensitized solar cell counter electrodes. The results found that scanning electron microscopy reveals the polyaniline-island forming on the FTO conductive glass for all four deposition times. The polymer-island size and film thickness increase with the deposition duration. The performance of polyaniline based dye-sensitized solar cells is dependent upon polymer thickness. The highest energy conversion efficiency of the polyaniline based dye-sensitized solar cells was ~6.02%, obtained from the 60-min polyaniline electrode and the lowest efficiency is ~ 5.34 % was found to be in the case of 180-min electrode. The polymer deposition duration above 60 min degrades the solar cell efficiency because of the decreasing of film catalytic activity as observed by cyclic voltammogram measurement. Taking all the results together, 60-min polyaniline electrode has the best potentials for dye-sensitized solar cells application.